An Osgood Type Regularity Criterion for the 3D Boussinesq Equations - Qiang Wu; Lin Hu; Guili Liu (The Scientific World Journal)
We consider the three-dimensional Boussinesq equations, and obtain an Osgood type regularity criterion in terms of the velocity gradient.